Enhances Lungs and Liver Function Using High-Intensity Interval Training in Individuals of Post-COVID-19 Infection - Tank, Arvind; Baldha, Garish; Ramchandran, Arunachalam; Dave, Vaibhav; Oza, Prachi (Journal of Neonatal Surgery, 2025)
COVID-19 affects several organs. Besides lung injury, the kidneys and liver can be damaged. This study determined Lungs and liver function changes after modified high-intensity interval training (HIIT) in individuals post-COVID-19 infection. eighty men and women who leaves in Pipar City Jodhpur had experienced COVID-19, aged 18 to 60 years were enrolled. The participants were randomly divided into 2 Groups: (a) the Control Group (n = 40): did not receive any exercise training program for 8 weeks; and the (b) HIIT Group (n = 40), received an 8 week-HIIT using leg cycling for 28 min·d-1, 3 times·wk-1. Lungs and liver function including metabolism of xenobiotics, endogenous hormones rate, and Pulmonary Function Test (PFT) were determined before and after the 8-wk program. The statistical results showed that metabolism of xenobiotics was significantly decreased (P = 0.021), PFT and Alanine Aminotransferase (ALT)was significantly increased (P = 0.008) in the HIIT Group; whereas, no changes were observed in the Control Group. However, there were no significant differences between the Groups. Also, the PFT were significantly changed in both Groups and were not different between Groups. The results suggest that Lungs function, such as metabolism of xenobiotics and PFT in individuals post-COVID-19 infection can be enhanced by HIIT. pulmonary function test is a lung function test. A spirometry test measures the flow of air through your lungs and estimates the amount of air in your lungs. It also tells your healthcare provider how strong your lungs are and how well you breathe.